The adsorption of water by active carbons, in relation to the enthalpy of immersion - Stoeckli, Fritz; Kraehenbuehl, F.; Morel, D. (My University, 1983)
It is shown that there exists a simple relation between the enthalpy of immersion of pure active carbons into water, and the number of so-called primary adsorption sites a0 derived from the water adsorption isotherm by using the new Dubinin-Serpinsky equation. The adsorption sites left on the surface after outgassing near 400°C, probably of the carbonyl type, contribute to the enthalpy of immersion by −25 kJ/mole, vs −0.6 kJ/mole for the bulk of the water filling the micropores at 307 K.